A comparative study on kinetics and dynamics of two dump truck lifting mechanisms using MATLAB simscape - Thong Duc Hong; Minh Quang Pham; Son Cong Tran; Lam Quang Tran; Truong Thanh Nguyen (Theoretical and Applied Mechanics Letters, 2024)
In this paper, two lifting mechanism models with opposing placements, which use the same hydraulic hoist model and have the same angle of 50°, have been developed. The mechanical and hydraulic simulation models are established using MATLAB Simscape to analyze their kinetics and dynamics in the lifting and holding stages. The simulation findings are compared to the analytical calculation results in the steady state, and both methods show good agreement. In the early lifting stage, Model 1 produces greater force and discharges goods in the container faster than Model 2. Meanwhile, Model 2 reaches a higher force and ejects goods from the container cleaner than its counterpart at the end lifting stage. The established simulation models can consider the effects of dynamic loads due to inertial moments and forces generated during the system operation. It is crucial in studying, designing, and optimizing the structure of hydraulic-mechanical systems.